Platinum Concentration and Pathologic Response to Cisplatin-Based Neoadjuvant Chemotherapy in Muscle-Invasive Bladder Cancer - Guancial, Elizabeth A.; Kilari, Deepak; Xiao, Guang-Qian; Abu-Farsakh, Sohaib H.; Baran, Andrea; Messing, Edward M.; Kim, Eric S. (PLOS ONE, 2016)
Background Platinum (Pt)-based chemotherapy is the standard of care for muscle-invasive bladder cancer (MIBC). However, resistance is a major limitation. Reduced intratumoral drug accumulation is an important mechanism of platinum resistance. Our group previously demonstrated a significant correlation between tissue Pt concentration and tumor response to Pt-based neoadjuvant chemotherapy (NAC) in lung cancer. We hypothesized that increased Pt concentration in radical cystectomy (RC) specimens would correlate with improved pathologic response to Pt-based NAC in MIBC. Methods A cohort of 19 clinically annotated, archived, fresh frozen RC specimens from patients with MIBC treated with Pt-based NAC was identified [ypT0 (pathologic complete response, pCR), N = 4; ≤ypT1N0M0 (pathologic partial response, pPR), N = 6; ≥ypT2 (minimal pathologic response/progression), N = 9)]. RC specimens from 2 patients with MIBC who did not receive NAC and 1 treated with a non-Pt containing NAC regimen were used as negative controls. Total Pt concentration in normal adjacent urothelial tissue and bladder tumors from RC specimens was measured by flameless atomic absorption spectrophotometry. Results Total Pt concentration in normal urothelium differed by tumor pathologic response (P = 0.011). Specimens with pCR had the highest Pt concentrations compared to those with pPR (P = 0.0095) or no response/progression (P = 0.020). There was no significant difference in Pt levels in normal urothelium and tumor between pPR and no response/progression groups (P = 0.37; P = 0.25, respectively). Conclusions: Our finding of increased intracellular Pt in RC specimens with pCR following NAC for MIBC compared to those with residual disease suggests that enhanced Pt accumulation may be an important determinant of Pt sensitivity. Factors that modulate intracellular Pt concentration, such as expression of Pt transporters, warrant further investigation as predictive biomarkers of response to Pt-based NAC in MIBC.